Extraction and Separation of Nano-Sized Zirconia from in High Purity ZrO(NO\(_3\))\(_2\) Using PC88A, D2EHPA and Determination of Impurities by ICP-MS - Nhuong Chu Manh; N. T. H. Lan; M. X. Truong; D. T. Huong; N. T. T. Loan (Challenges and Advances in Chemical Science Vol. 5, 2021)
Many components of nuclear reactors, particularly fuel cladding tubes, require high purity zirconium (Zr) elements. Because of the influence of the matrix, determining impurities in Zr materials necessitates separation from the Zr matrix. Solvent extraction is a common extraction process that is appropriate for large-scale production. In this chapter, extraction capability of Zr(IV) by 2-ethylhexyl phosphonic acid mono 2-ethylhexyl ester (PC88A) and di-(2-ethylhexyl) phosphoric acid (D2EHPA) were examined by FT-IR, UV spectra of ZrO(NO3)2 salt, PC88A-toluene solvent, and Zr-PC88A-toluene complex. ZrO2 (obtained from Institute for Technology of Radioactive and Rare Elements - ITRRE) and ZrCl4 (Merck) are transferred to ZrO(NO3)2, after being separated from the Zr matrix, was determined for impurities using internal standard (indium, In) by 50% of PC88A dissolved in toluene. Impurities were separated from the Zr matrix in two steps. First, the Zr matrix and impurities were extracted in 3.0 M HNO3 using 50 percent PC88A/toluene for one cycle. Second, impurities were cleaned in two cycles with 4.0-6.0 M HNO3. According to the findings, approximately 74% of Zr(IV) was separated into the organic phase, while 26% remained in the aqueous phase. The recovery of impurities following separation from the Zr matrix by ICP-MS using an internal standard demonstrated a 95–100% recovery of impurities.The influence of the Zr matrix on ICP-MS element determination is insignificant with the amount of Zr stated. Impurity levels having relative standard deviations (RSDs) of less than 6.9% and recoveries (Revs) of 88.6–98.8 percent. As a result, the assessment of contaminants is extremely accurate and reliable. Back-extraction of Zr(IV) in organic phase with 1.0 - 1.5 M H2SO4 removed 99.5 percent of the Zr matrix and returned it to the aqueous phase. After that, after back-extraction, NH3 was added to the solution containing Zr to make Zr(OH)4, which was then desiccated to yield ZrO2. The new ZrO2 product has a spherical nanostructure with diameters of less than 25 nm, which is suitable for applications such as colourant treatment, metal ions in wastewater sources, and the manufacture of anti-corrosion steel, according to X-ray Diffraction (XRD), scanning and transmission electron microscopy (SEM and TEM) images. Furthermore, the new ZrO2 product’s energy dispersive X-ray (EDX) analysis revealed that it is extremely pure.